Determining Intrapersonal Indicators For Green Skills Development: A Systematic Review and Framework In Vocational Education - Muhammad Utsman Amrul Hamzah; Ivan Hanavi; Constantinus Rudy Prihantoro (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2026)
The integration of green skills (GS) into vocational high school (VHS) curricula has expanded, yet specific indicators of the intrapersonal competence (IaC) domain as the foundation for long-term sustainable behavior remain underexplored. This study aims to formulate a measurable IaC indicator framework to support green skills development in vocational education. Employing a Systematic Literature Review (SLR) guided by the PRISMA flowchart and a meta-synthesis approach, this study analyzed 19 peer-reviewed articles published between 2021 and 2026 from ERIC and Google Scholar databases. Findings reveal that although GS integration urgency is broadly acknowledged, few studies provide explicit, measurable IaC indicators within the vocational context. This study contributes a synthesized IaC framework encompassing self-awareness and responsibility as core indicators. The framework offers a practical pathway for educators, students, and institutions in constructing curricula that effectively integrate green skills development within vocational education settings.